What Is the Role of AI in Mental Health Diagnosis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Artificial intelligence (AI) is rapidly transforming various sectors, and healthcare is no exception. Within the medical field, one of the most promising and...
Keywords: AI in Mental Health; Mental; Health; Diagnosis; Artificial Intelligence; Machine Learning; Healthcare